2009
DOI: 10.4103/0378-6323.55406
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of skin diseases among patients attending a tertiary care teaching hospital in kerala

Abstract: and other aspects of factitious wealing (dermographism). Br J Dermatol 1971;85:331-5. 4. Kaplan A.P., Clinical practice: Chronic urticaria and angioedema. N Engl J Med 2002;346:175-9. 5. Mathews CN, Kirby JD, James J, Warin RP. Dermographism: reduction in wheal sizeby chlorpheniramine and hydroxyzine. Br J Dermatolol 1973;88:279-82. 6. Ryan TJ, Shim-Young N, Turk JL, Delayed pressure urticaria. Br J Dermatol 1968;80:485-90. 7. Godse KV. Diagnosis of delayed pressure urticaria. Indian J Dermatol Venereol Leprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
17
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 0 publications
12
17
1
Order By: Relevance
“…The study performed by Das et al, 6 reported that psoriasis (7.7%) is least in its incidence among major dermatological diseases found in that part of India. Our study revealed that incidence of Hansen's disease is only 2.04%, which is similar with study of Das et al, 6 and is less than that of Das et al, 6 and Chatterjee 27 and is more than the reported percentage in the study observed by Rao et al 8 and Devi et al, 11 Asokan et al 27 This variation in disease pattern might be because the pattern of skin diseases are influenced by various factors such as religion, race, occupation, nutritional habits, etc. 4 and also transmissible skin diseases are observed generally in people living in poor socioeconomic and unhygienic conditions.…”
Section: Discussionsupporting
confidence: 91%
“…The study performed by Das et al, 6 reported that psoriasis (7.7%) is least in its incidence among major dermatological diseases found in that part of India. Our study revealed that incidence of Hansen's disease is only 2.04%, which is similar with study of Das et al, 6 and is less than that of Das et al, 6 and Chatterjee 27 and is more than the reported percentage in the study observed by Rao et al 8 and Devi et al, 11 Asokan et al 27 This variation in disease pattern might be because the pattern of skin diseases are influenced by various factors such as religion, race, occupation, nutritional habits, etc. 4 and also transmissible skin diseases are observed generally in people living in poor socioeconomic and unhygienic conditions.…”
Section: Discussionsupporting
confidence: 91%
“…By review various reports, we find that almost all studies mentioned here[2357891011] are compatible with our reports i.e., the commonest skin disease is of infective origin, followed by allergic diseases except two reports,[412] which show the reverse situation. But, the reports of two developed countries[1314] show opposite reports of one another.…”
Section: Discussionsupporting
confidence: 89%
“…There is good similarity between our study and a report from neighouring state of Assam[2] about infective dermatoses, eczema, non-malignant papulosquamous disorder, acne, melanodermatoses, hair disorders, vesiculo-bullous disorder, skin and appendegeal tumors, and also very close to another Indian study[8] in infective and acne disorders but wide deviation from other Indian study[3] about infective diseases. This indicates geographic position of study center.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[1][2][3] Further, this trend was noticed in our present study with noninfective skin diseases accounting for 58.7% cases. However, some other studies have reported higher prevalence of infective skin diseases varying from 35.2% to 59.1%.…”
supporting
confidence: 67%